Implementasi Pendidikan Integral Di Sekolah Menengah Agama Ibrah Permatang Pauh Penang Malaysia - Nuraini, Indah Ayu; Aziz, Baqi Rafika (MOMENTUM : Jurnal Sosial dan Keagamaan, 2024)
This study discusses the implementation of integral education in the Ibrah Religion Middle School, Permatang Pauh Penang Malaysia. The purpose of this study are: 1) to describe the implementation of integral education at the Ibrah Religion Middle School, Penang Malaysia. 2) Knowing the obstacles in implementing integral education. 3) Knowing the solutions provided to deal with obstacles in implementing integral education. This research uses descriptive and the approach used is qualitative. limiting research to the focus or formulation of the problem and using the characteristics that are in accordance with qualitative research, the subject of this research is students and teachers at the Ibrah Religion Middle School, Penang Malaysia. Data collection techniques used were observation, documentation, and interviews. The results were obtained that the implementation of integral education in the Ibrah Religion Middle School has been applied by all teachers and students through habituation or tradition that instills religious values both at school and in the dormitory. There are several obstacles in implementing integral education both from the teacher and students, namely the lack of understanding of the teacher and the family background of students, because to implement spiritual education needs support from the family since childhood so that to develop and integrate spiritual education with cognitive will be easier. The effort made is to approach the individual regularly because the management of spiritual values requires habituation which is carried out every day. The resulting output is to become a dignified student who always adheres to Islamic law because the main pillar of the School of Religious Affairs is the Islamic Tarbiyah